2020
DOI: 10.3390/catal10111318
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Activated Carbons for the Treatment of Highly Concentrated Phenol Solutions Using Catalytic Wet Peroxide Oxidation: The Effect of Iron Impurities on the Catalytic Activity

Abstract: Activated carbons (ACs) have been used as metal supports for catalytic wet peroxide oxidation (CWPO) of organic compounds. A shortcoming is that added metals can undergo leaching, leading to catalyst deactivation and secondary contamination of the treated water. In the present study, CWPO of phenol aqueous solutions was investigated in the presence of five commercial ACs without added metals yet containing different extents of iron impurities resulting from their industrial preparation procedures (ROX 0.8, RX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Incipient Wetness Impregnation (IWI) [12][13][14][15][16] technology was employed in preparing the novel nano-catalyst. At first, AC was treated and dried so as to eliminate any impurities before being utilized in the IWI process.…”
Section: Incipient Wetness Impregnation (Iwi) Processmentioning
confidence: 99%
“…Incipient Wetness Impregnation (IWI) [12][13][14][15][16] technology was employed in preparing the novel nano-catalyst. At first, AC was treated and dried so as to eliminate any impurities before being utilized in the IWI process.…”
Section: Incipient Wetness Impregnation (Iwi) Processmentioning
confidence: 99%
“…It is known that the activity of catalysts in CWPO strongly depends on the capacity of electron exchange of their active sites for the generation of hydroxyl and hydroperoxyl radicals from hydrogen peroxide decomposition and further oxidation of organic substances present in the aqueous matrix [37]. Several works have reported the role of oxygen-containing groups and related acid-base characteristics [38], residual metallic particles [38,39], defect sites [40], the presence of heteroatoms [41,42] and textural properties [43] in the abatement of different pollutants. We observed that both catalysts led to similar conversions since removals of 43% and 41% for TOC, 52% and 45% for COD, 93% and 91% for BOD 5 , 82% and 79% for aromaticity, and 43% and 42% of η H 2 O 2 were obtained with HC and PC, respectively.…”
Section: Cwpo Of Leachate Waters As a Single Stepmentioning
confidence: 99%
“…However, there are some evidence that carbon nanotubes impurities can enhance redox properties of carbon and improve electrooxidation of organics 34 , 35 . In turn, iron impurity of activated carbons can enhance phenol removal in catalytic wet peroxidation 36 . In our previous work 29 , it was shown that the mineral matter presence in activated carbon enhances the ozone decomposition.…”
Section: Introductionmentioning
confidence: 99%